2016
DOI: 10.1039/c6md00269b
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between drugs with short and long residence times

Abstract: The kinetic aspects of the ligand–receptor interaction, characterising the residence time of a ligand in its binding site, play an important role in drug effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 11 publications
(9 reference statements)
3
7
0
Order By: Relevance
“…This effect is caused by the fact that the protein is depleted faster in the presence of unlabeled compound, which also induces a slowly dissociating complex, leaving less free DAT in the protein pool for the radioligand to bind to, resulting in an increase of k obs . This indicates the presence of a slow step in unlabeled ligand binding and it is similar to the effect caused by PE2I, as reported before ,. For these ligands, the K L and K i values are not similar, i. e. without the isomerization step the protein's affinity for the compounds would be much lower.…”
Section: Figuresupporting
confidence: 79%
See 2 more Smart Citations
“…This effect is caused by the fact that the protein is depleted faster in the presence of unlabeled compound, which also induces a slowly dissociating complex, leaving less free DAT in the protein pool for the radioligand to bind to, resulting in an increase of k obs . This indicates the presence of a slow step in unlabeled ligand binding and it is similar to the effect caused by PE2I, as reported before ,. For these ligands, the K L and K i values are not similar, i. e. without the isomerization step the protein's affinity for the compounds would be much lower.…”
Section: Figuresupporting
confidence: 79%
“…We report the results of a systematic kinetic analysis of the interaction of a series of N ‐substituted 2β‐carbomethoxy‐3β‐(4′‐methylphenyl)‐nortropane derivatives with DAT, using [ 3 H]PE2I as the reporter ligand as described in our previous report . It was shown that ligands can interact with DAT by two different mechanisms: (i) a one‐step equilibrium binding process and (ii) a two‐step process where the second step is a slow isomerization of the complex (Scheme ), and these two mechanisms can be differentiated by kinetic study of the ligand–receptor interaction ,…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This fast step is followed by the slow step of the PE2I-DAT* complex isomerization, and the proposed methods of kinetic analysis allow for the determination of the parameters K L , k i , and k −i . 20 The presence of the slow, complex isomerization process significantly shifts the equilibrium between the free and ligand-bound DAT sites. Therefore, it is possible that this process also affects tracer trafficking between compartments C ND and C S in Scheme 2.…”
mentioning
confidence: 99%
“…As the values of these rate constants increase hyperbolically with increasing ligand concentration (Figure 1, right panel), it can be concluded that FE-PE2I interaction with DAT follows the reaction mechanism shown in Scheme 3, as this ligand induces the slow isomerization step, characterized by rate constants k i and k −i . 21 Principles of this experimental approach were described in detail in our previous works, 20 and the results obtained were used for calculation of kinetic parameters K L , k i , and k −i for FE-PE2I interaction with DAT by using eqs 2 and 3 (see Supporting Information).…”
mentioning
confidence: 99%